Construction of ecological sense in reterritorialization in the Ticas Community, in the Province of Cordoba (Huellas, 2021)
This work addresses the process of communal reorganization and contemporary reterritorialization of Ticas Community (Bialet Massé and San Carlos Minas) of the province of Cordoba between 2013 and 2017. The aim of this work is to analyze the relationship between these processes and the construction of sense of belonging in relation to indigenous identity. The one that is considered as an ecological identity and whose territorial practices are grouped in a series of possible alternatives to the local / regional dynamics of community alterity. In this sense, a series of statements and actions carried out in the claimed territory called Cochatalasacate from the period of reoccupation by the community are described. These actions enter into dialogue and conflict with non-indigenous social actors who settle in the claimed territory. The analysis is based on material surveyed from the PhD research itself, which is already finished. The methodology with a qualitative and particularly ethnographic approach implied field work involving participant observation and in-depth interviews with community members in the territory. There is also an analysis of information collected outside the period of time subject of the field work (prior to 2013), such as social media posts and collective mapping material.
Keywords: reterritorialization; Ticas community; socio-environmental lines; decoloniality of territory